Surface modification of polyurethane with a hydrophilic, antibacterial polymer for improved antifouling and antibacterial function. (September 2018) - Xie, Dong; Howard, Leah; Almousa, Rashed
Antimicrobial surface is important for the inhibition of bacteria or biofilm formation on biomaterials. The objective of this study was to immobilize a novel hydrophilic polymer containing the antibacterial moiety onto polyurethane surface via a simple surface coating technology to make the surface not only antibacterial but also antifouling. The compound 3, 4-dichloro-5-hydroxy-2(5H)-furanone was derivatized, characterized and incorporated onto polyvinylpyrrolidone containing succinimidyl functional groups, followed by coating onto the polyurethane surface. Contact angle, antibacterial function and protein adsorption of the modified surface were evaluated. The result shows that the modified surface exhibited significantly enhanced hydrophilicity with a 54–65% decrease in contact angle, increased antibacterial activity to Staphylococcus aureus, Staphylococcus epidermidis, and Pseudomonas aeruginosa with a 24–57% decrease in viability, and reduced human serum albumin adsorption with a 64–70% decrease in adsorption, as compared to the original polyurethane.